Why animals talk : the new science of animal communication - Kershenbaum, Arik (Penguin Press, 2024)
"From leading zoologist Arik Kershenbaum, a delightful and groundbreaking exploration of animal communication and its true meaning. Animal communication has forever seemed intelligible. We are surrounded by animals and the cacophony of sounds that they make-from the chirping of songbirds to the growls of lions on the savanna-but we have yet to fully understand why animals communicate the way they do. What are they saying? This is only part of the mystery. To go deeper, we must also ask, what is motivating them? Why Animals Talk is an exhilarating journey through the untamed world of animal communication. Following his international bestseller, The Zoologist's Guide to the Galaxy, acclaimed zoologist Arik Kershenbaum draws on extensive original research to reveal how many of the animal kingdom's most seemingly confusing or untranslatable signals are in fact logical and consistent-and not that different from our own. His fascinating deep dive into this timeless subject overturns decades of conventional wisdom, inviting readers to experience for the first time communication through the minds of animals themselves. From the majestic howls of wolves and the enchanting chatter of parrots to the melodic clicks of dolphins and the spirited grunts of chimpanzees, these often strange expressions are far from mere noise. In fact, they hold secrets that we are just beginning to decipher. It's one of the oldest mysteries that has haunted Homo sapiens for hundreds of thousands of years: Are animals talking just like us, or are we the only animals on the planet to have our own language?"--